Lightweight Design of Drive Axle Housing based on OptiStruct - Xiaofei Song; Ronghui Lin; Shuaichao Li; Yunfa Qiao; Yulong Ji; Juan Deng; Zhitian Guo (Jixie chuandong)
As an important part of automobile， the lightweight design of the driving axle housing must be carried out to meet the requirements of its stiffness and strength. In order to ensure the performance requirements， the traditional design concept generally adopts redundant design. Based on the integrated technology of CAD/CAE， the joint design between 3D mathematical model and finite element model is adopted， and the lightweight design of the driving axle housing is realized based on the size optimization algorithm of OptiStruct. The drive axle housing model created by CATIA is introduced into HYPERMESH for pre-processing， the calculation conditions and boundary conditions are designed and proposed. The statics， dynamics analysis and fatigue analysis are used to verify that the drive axle housing meets the use standard. Then the optimization analysis is conducted in the OptiStruct solver， and several iterative calculations are used to get the analysis result. The mass of the optimized axle housing is 152.042 kg， which is reduced by 50.075 kg， and the weight loss reaches 24.78%， and then the optimized drive axle housing is analyzed. Finally， the fatigue bench test of the optimized axle housing is carried out. The analysis and experimental results show that the optimized axle housing meets the test standard and a certain reference value for lightweight design of the same type is provided.